Music How It Came to Be What It Is - Smith, Hannah (Cambridge library collection. Music, 1898)
Hannah Smith (1849–1939) was a composer for children and an educator. In 1903 she published the popular Founders of Music, a series of biographical sketches of composers written for children. Written in 1898, when Wagner had been dead for only fifteen years, this is a concise history of music and instruments, aimed at the enthusiast. Covering broad subjects rather than concentrating on a few composers, Smith discusses not just the development of musical styles but also how musical notation developed, how the ear functions and how musical instruments produce the sounds they do. The tastes of the time are evident, particularly in the surprisingly detailed discussion of the Oratorio: however, the book allows us to see how music and its progress were regarded at the turn of the twentieth century, before composers such as Stravinsky and Schoenberg shook the musical establishment